Changes in structural groups in dough and bread from wheat flour with the addition of rice flour - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana (My University, 2023)
Bakery industry is developing rapidly, being one of the main branches in the food industry, the range of products is increasing, and technologies are being improved. Traditionally, in the technology of bakery products, wheat flour is used as a main raw material with gluten content, which is able to form the gluten framework of products. However, other types of flour are also used, in particular rice flour. Швидкими темпами розвивається хлібопекарська промисловість, яка є однією з основних галузей харчової промисловості, збільшується асортимент продукції, удосконалюються технології. Традиційно в технології хлібобулочних виробів в якості основної сировини використовують пшеничне борошно з вмістом клейковини, яка здатна утворювати клейковину каркаса виробів. Однак використовуються і інші види борошна, зокрема рисове.
Keywords: кафедра фізики та професійної безпеки; wheat flour; rice flour; infrared spectroscopy method; пшеничне борошно; рисове борошно; метод інфрачервоної спектроскопії